The aryl hydrocarbon receptor as a tumor modulator: mechanisms to therapy - Chaudhry, Kanita A.; Bianchi-Smiraglia, Anna (Frontiers in Oncology, 2024)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that is widely recognized to play important, but complex, modulatory roles in a variety of tumor types. In this review, we comprehensively summarize the increasingly controversial role of AhR as a tumor regulator and the mechanisms by which it alters tumor progression based on the cancer cell type. Finally, we discuss new and emerging strategies to therapeutically modulate AhR, focusing on novel agents that hold promise in current human clinical trials as well as existing FDA-approved drugs that could potentially be repurposed for cancer therapy.